2022
DOI: 10.3390/su141912703
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of rGO@TiO2 Photocatalyst for the Degradation of Organic Pollutants in Water

Abstract: The availability of clean water is essential for humans wellbeing and the diverse biotic population in the environment. Menkind imposes a significant pressure on food supplies, natural resources, and other commodities. Large-scale anthropogenic activities, such as agriculture and industry, which are practiced to ensure population growth and survival, have caused several harmful environmental effects, including the discharge of pollutants into the aquatic environment. Among them organic micropollutants (OMPs) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 98 publications
1
4
0
Order By: Relevance
“…TiO2 NPs were identified by using the Xray diffraction (XRD) technique to characterize the modified glassy carbon electrode paste (NPs TiO2@RGO/GCE), as shown in The obtained nanocomposites XRD pattern results reveal a highly crystalline TiO2 structure, no precursor-or reagent-related impurity peaks, and the absence of GO diffraction peaks in the prepared TiO2/rGO composite, which shows that the GO has been effectively reduced and that there is stacking between the graphene sheets. These structural characterizations support the conclusion that the hydrothermal method used to immobilize TiO2 on rGO was successful [48,49] . The a and c axes are followed by a high number of (TiO2) crystals.…”
Section: X-ray Diffraction Analysis Of Tio2 -Nps @Rgo /Gcesupporting
confidence: 74%
“…TiO2 NPs were identified by using the Xray diffraction (XRD) technique to characterize the modified glassy carbon electrode paste (NPs TiO2@RGO/GCE), as shown in The obtained nanocomposites XRD pattern results reveal a highly crystalline TiO2 structure, no precursor-or reagent-related impurity peaks, and the absence of GO diffraction peaks in the prepared TiO2/rGO composite, which shows that the GO has been effectively reduced and that there is stacking between the graphene sheets. These structural characterizations support the conclusion that the hydrothermal method used to immobilize TiO2 on rGO was successful [48,49] . The a and c axes are followed by a high number of (TiO2) crystals.…”
Section: X-ray Diffraction Analysis Of Tio2 -Nps @Rgo /Gcesupporting
confidence: 74%
“…In continue, these and ˙OH radicals react with MB dye molecules (RH) to degrade them into non-hazardous compounds. 50,51 The reactions involved in the rGO/NiO x /Ag photocatalysis with the presence of MB molecules are given as follows:˙OOH + ˙OOH → H 2 O 2 + O 2 h + (VB) + H 2 O → ˙OH + H + h + (VB) + OH → ˙OH˙OH + RH → R˙ + H 2 O…”
Section: Resultsmentioning
confidence: 99%
“…With over 10,000 colors used across various applications in the industrial sector, synthetic colors are reported to be produced in substantial quantities, reaching an annual total of 30,000 tons [36]. Numerous synthetic dyes possess carcinogenic properties, posing a threat to human health, while their ability to reduce light permeability into water bodies negatively impacts algae and other aquatic life [37]. In human biology, dyes can adversely affect enzyme levels such as gamma-glutamyl transferase and alkaline phosphatase, impacting the liver and the central nervous system.…”
Section: Responsible Dyes For Water Pollutionmentioning
confidence: 99%